2021
DOI: 10.5935/jetia.v7i28.741
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the recent periods of oat market in Turkey

Abstract: Recently, the demand for sufficient and safe food has been increasing, and alternative food sources have gained importance. Oat, which is in the cereals group, is used in animal breeding besides being a human food. Turkey, while in the twentieth in the world in terms of production, is ranked thirty-second in terms of efficiency. The purpose of this study, the production quantity of oat market in recent years in Turkey, cultivation area, yield, average selling price, exports, imports, and foreign trade balance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…When the structure of olive cultivation in Turkey is analysed, it is observed that although there was a significant rise in the olive grove and the number of trees between 2004 and 2022, the same is not observed in the yield per tree (TÜİK, 2023). The main reasons why Turkey has not been able to achieve the output growth that other countries with which Turkey competes in olive cultivation have achieved in recent years are low productivity and unfavourable climatic factors that increase the tendency of periodicity (Bayramer, 2015;Şahin and Aydoğdu, 2021). Also, harvesting every 2-3 years due to the harsh periodicity of local varieties in the South-eastern and Mediterranean regions causes the olive groves in those regions to be abandoned to their own fate for a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…When the structure of olive cultivation in Turkey is analysed, it is observed that although there was a significant rise in the olive grove and the number of trees between 2004 and 2022, the same is not observed in the yield per tree (TÜİK, 2023). The main reasons why Turkey has not been able to achieve the output growth that other countries with which Turkey competes in olive cultivation have achieved in recent years are low productivity and unfavourable climatic factors that increase the tendency of periodicity (Bayramer, 2015;Şahin and Aydoğdu, 2021). Also, harvesting every 2-3 years due to the harsh periodicity of local varieties in the South-eastern and Mediterranean regions causes the olive groves in those regions to be abandoned to their own fate for a long period of time.…”
Section: Introductionmentioning
confidence: 99%